2010
DOI: 10.1016/j.ijmedinf.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Organisational influences on nurses’ use of clinical decision support systems

Abstract: ObjectiveNurses are increasingly using computerised decision support systems (CDSS) to support their practice. Previous studies have highlighted the importance organisational factors have on the successful implementation of new technologies in healthcare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…However the findings from this study clearly underscore that, to successfully implement and sustain e-health applications in daily practice, the users must recognize that it is beneficial in their daily work and for the patients [52,53]. Understanding a tool's utility affects the motivation both to use the system and to encourage the patient to participate [54].…”
Section: Observabilitymentioning
confidence: 85%
“…However the findings from this study clearly underscore that, to successfully implement and sustain e-health applications in daily practice, the users must recognize that it is beneficial in their daily work and for the patients [52,53]. Understanding a tool's utility affects the motivation both to use the system and to encourage the patient to participate [54].…”
Section: Observabilitymentioning
confidence: 85%
“…The impact of a CDSS on nurses' decision making must be explored in future research [59]. Studies have shown that implementing an EHR does not unilaterally indicate that documentation comprehensiveness will increase [38,60].…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors in health care organization that can have an impact on information systems such as organizational culture that is one of the most important factors in the success of technology implementation (Randell et al, 2010). Flexible organizational structure and leadership behaviors and providing an environment in which innovation in organizations is appreciated facilitate moving towards technologies (Vaccaro et al, 2012).…”
Section: Health Care Organizationmentioning
confidence: 99%